(Pre)Modern sleep. New evidence from the Antwerp criminal court (1715–1795). (11th June 2020) - Verhoeven, Gerrit
Abstract: Lately, experts have turned to historical evidence to uncover the default mode of our sleep pattern. Even though there are some notable exceptions, most historians use a qualitative methodology based on scattered evidence in diaries, letters, novels, medical treatise and other literary sources. To provide fresh perspective in the debate, the present article develops a more quantitative approach. Drawing fresh evidence from early modern criminal records – viz the eyewitness reports of the Hoge Vierschaer or the local criminal court in Antwerp – we are able to debunk some classic stereotypes about premodern sleep patterns. Data reveal that most 18 th ‐century Antwerpers slept fewer hours than we would expect, slumbered in a monophasic way and rarely if ever took a nap during the day. Moreover, the start and end of sleep were less attuned to the solar cycle than we would imagine. Last but not least, the pattern also shows some fascinating weekly and seasonal variations.